PENGARUH PENGGUNAAN MEDIA PAPAN PINTAR PERKALIAN TERHADAP KETERAMPILAN BERHITUNG KELAS III SDN 105288 DESA SEI ROTAN - Riri Mayuni; Nabila Zahra Salsabila lubis; Sindi Fathika Sari; Nuraisyah Sipahutar; Meliyani Sari Sitepu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
According to research carried out by researchers at SDN 105288 Desa Sei Rotan, most teachers, especially mathematics teachers, use the lecture method in teaching and learning activities. This method can make student passive and not interested in learning. The aim of this research is to find out is the use of multiplication smart board media effective in improving numeracy skills of class III students at SDN 105288 Desa Sei Rotan. Method used is a quantitative method, in the form of a pretest and posttest. Sample the research consisted of 21 class III students. Based on the results of the pretest and posttest carried out, show a higher average percentage of posttest completeness compared with the pretest. The average obtained by the pretest was 82%, meanwhile posttest 92%. This means that there is an influence of the use of board media smart multiplication on counting skills in class III multiplication material SDN Desa Sei Rotan.